Steel fiber unsaturated polyester polymer concrete applied to road emergency repair and preparation method thereof

By optimizing the mix ratio of steel fiber unsaturated polyester polymer concrete and adding an appropriate amount of steel fiber, the problem of insufficient research on the impact of steel fiber replacement rate on the mechanical properties of concrete is solved, and the preparation of high-performance concrete is achieved, which can be quickly and effectively Repair municipal roads.

CN119461982APending Publication Date: 2025-02-18GUANGZHOU ENG CONTRCTOR GRP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671607.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, there are few studies on the impact of steel fiber substitution rate on the mechanical properties of municipal road emergency restoration concrete, resulting in limited promotion and application of steel fiber unsaturated polyester polymer concrete in emergency repair of municipal roads.

Method used

Optimize the mix ratio of steel fiber unsaturated polyester polymer concrete, adjust the proportion of unsaturated polyester resin, curing agent, accelerator, cement, natural river sand, and natural gravel, and add 0 to 1.5% to the concrete steel fiber unsaturated polyester polymer concrete suitable for road emergency repair was prepared.

Benefits of technology

The mechanical properties of steel fiber unsaturated polyester polymer concrete are maximized, which significantly enhances the compressive strength, crack resistance, toughness and durability of concrete, and can quickly repair municipal roads and meet the needs of emergency repairs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461982A_ABST
    Figure CN119461982A_ABST
Patent Text Reader

Abstract

The invention discloses a steel fiber unsaturated polyester polymer concrete applied to road emergency repair and a preparation method thereof, and the preparation method comprises the following steps: stirring natural broken stone, natural river sand, cement and steel fiber in a concrete mixer for 60 seconds, then adding a curing agent into resin, stirring for 30 seconds, then adding an accelerant into the mixture, mixing for 30 seconds, and finally adding a curing agent into the mixture, and stirring for 30 seconds to obtain the steel fiber unsaturated polyester polymer concrete. And finally, adding the resin mixture into a concrete mixer, and mixing with the solid material for 120 seconds to obtain the steel fiber unsaturated polyester polymer concrete. According to the invention, the unsaturated polyester resin, the curing agent, the accelerant (cobalt iso-octoate) and the steel fiber are efficiently utilized and mixed to form the curing-free and vibration-free super-early-strength and high-performance concrete. According to the invention, while resources are saved, the compressive strength, crack resistance, ductility and durability of the concrete are remarkably enhanced. The preparation process is simple and easy to operate, has a good application prospect, and can be widely applied to pavement emergency repair engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of municipal road emergency repair materials, in particular to a steel fiber unsaturated polyester polymer concrete used for road emergency repair and a preparation method thereof. Background Art

[0002] With the rapid advancement of urbanization in my country, the volume of urban traffic and municipal highway transportation has increased dramatically. As the road surface is exposed to the open air for a long time, subjected to the sun, rain, high temperature, rain, snow and other freeze-thaw environments, and subjected to vehicle impact and cyclic loads for a long time, the concrete pavement layer will crack, the protective layer will peel off, and even the bearing layer will fail completely. Therefore, the demand for rapid repair of municipal highway pavements is increasing. However, the traditional concrete pavement layer repair is time-consuming and laborious, and the maintenance conditions are extremely harsh, which can not achieve the purpose of emergency repair and rapid opening of traffic. Based on existing research and actual needs, the development of an early-strengthening and fast-hardening concrete is imminent.

[0003] In order to change the serious drawbacks of traditional cement concrete repair methods that "repair in one day, maintain for a long time" and cause traffic congestion, the research and development of materials and processes for rapid repair of road emergency repairs has become a hot topic at home and abroad. Domestic and foreign scholars' research on high-performance repair materials mainly focuses on the following three categories: ① Inorganic repair materials; ② Organic repair materials; ③ Composite repair materials. However, there are few studies on steel fiber unsaturated polyester polymer concrete at present, and the synergistic working mechanism between steel fiber unsaturated polyester polymer and various components of concrete has not been explored. There are few research data and theoretical basis, especially the influence of steel fiber volume incorporation rate on the mechanical properties of concrete. This greatly restricts the promotion and application of steel fiber unsaturated polyester polymer concrete in municipal road emergency repairs. How to develop a maintenance-free, vibration-free ultra-early strength, high-performance concrete has become the key to this technology. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of the influence of steel fiber replacement rate on the mechanical properties of municipal pavement emergency repair concrete in the above-mentioned prior art, to provide a steel fiber unsaturated polyester polymer concrete used for road emergency repair and a preparation method thereof, to optimize the mix ratio of steel fiber unsaturated polyester polymer concrete, to maximize the mechanical properties of steel fiber unsaturated polyester polymer concrete, to promote the green and environmentally friendly development of high-performance concrete materials in my country, and to further promote the application of steel fiber unsaturated polyester polymer concrete in municipal pavement emergency repair.

[0005] The present invention is achieved through the following technical solutions:

[0006] A steel fiber unsaturated polyester polymer concrete used for emergency road repair, wherein the steel fiber unsaturated polyester polymer concrete is composed of the following components in a mass ratio: unsaturated polyester resin: curing agent: accelerator: cement: natural river sand: natural crushed stone = 6.8:1:0.5:7.6:34:41.6, wherein the amount of steel fiber accounts for 0-1.5% of the volume of the steel fiber unsaturated polyester polymer concrete mixture.

[0007] As a further improvement of the technical solution of the invention, the basic physical properties of the unsaturated polyester resin are: density: 1.05-1.10 g / cm 3 , viscosity is 400-600MPa.s, acidity is 18-24mgKOH / g, and solid content is 63-69%.

[0008] As a further improvement of the technical solution of the invention, the steel fiber is an end hook type steel fiber; the diameter of the end hook type steel fiber is 0.75-0.85 mm, the length is 30-35 mm, the density is 7.85 g / cm3, the elastic modulus is 210 GPa, and the tensile strength is 400 MPa.

[0009] As a further improvement of the technical solution of the invention, the particle size of the natural gravel is 5 mm to 19 mm, and the particle size of the natural river sand is less than 4.75 mm.

[0010] As a further improvement of the technical solution of the invention, a method for preparing steel fiber unsaturated polyester polymer concrete for emergency road repair comprises the following steps:

[0011] Step S1. Mix all solid materials, including cement, natural river sand, natural crushed stone and steel fiber, in a concrete mixer for 60 seconds to obtain dry concrete;

[0012] Step S2. adding a curing agent to the unsaturated polyester resin, stirring for 30 seconds to obtain a mixture, and then adding an accelerator to the mixture and mixing for another 30 seconds to obtain a resin mixture;

[0013] Step S3. Add the resin mixture obtained in step S2 into the concrete mixer and mix it with the dry concrete for 120 seconds;

[0014] Step S4. Pour the mixture into a designed steel mold, compact it by tamping without vibration, and demould it after curing at room temperature for 3 hours. Then, cure the specimen under natural conditions indoors until it reaches the corresponding age for experiment.

[0015] The preparation process of the steel fiber unsaturated polyester polymer concrete of the present invention is easy to operate and realize.

[0016] The steel fiber unsaturated polyester polymer concrete includes but is not limited to applications in road emergency repairs.

[0017] In summary, the present invention has the following beneficial effects:

[0018] The present invention provides a steel fiber unsaturated polyester polymer concrete for road emergency repair and a preparation method thereof (hereinafter referred to as "SF-UPPC"), optimizes the mix ratio of SF-UPPC, can maximize the mechanical properties of SF-UPPC, and overcomes the defects of the traditional road repair method of "one day repair, long health" that is time-consuming, labor-intensive, and costly. Its research and development process is simple and easy to operate, has good application prospects, and can be widely used in municipal road emergency repair applications, and efficiently utilizes unsaturated polyester resin (UPR), curing agent (methyl ethyl ketone peroxide, MEKP) and accelerator (cobalt isooctanoate), and steel fibers are mixed to form a maintenance-free, vibration-free ultra-early strength, high-performance concrete. While saving resources, the present invention significantly enhances the compressive strength, crack resistance, ductility and durability of concrete. Its preparation process is simple and easy to operate, has good application prospects, and can be widely used in road emergency repair projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0020] Figure 1 This is a schematic diagram of an axial compression test of a cylinder using a MATEST material compression testing machine with a load upper limit of 4000 kN in an embodiment of the present invention;

[0021] Figure 2 This is a schematic diagram of a multifunctional static strain tester according to an embodiment of the present invention;

[0022] Figure 3 This is a schematic diagram of an embodiment of the present invention showing that as the content of steel fiber increases, the pores in the concrete become more and more numerous and larger, and when the volume content of the steel fiber reaches 1.5%, the concrete has already developed a honeycomb surface;

[0023] Figure 4 This is a schematic diagram of the test failure state of a cube specimen according to an embodiment of the present invention;

[0024] Figure 5 Schematic diagram of static compression response of SF-UPPC at different ages according to an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, features, and advantages of this application more obvious and easy to understand, the technical solutions in the embodiments of this application are clearly and completely described. Obviously, the embodiments described below are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] A steel fiber unsaturated polyester polymer concrete used for emergency road repair, wherein the steel fiber unsaturated polyester polymer concrete is composed of the following components in a mass ratio: unsaturated polyester resin: curing agent: accelerator: cement: natural river sand: natural crushed stone = 6.8:1:0.5:7.6:34:41.6, wherein the amount of steel fiber accounts for 0-1.5% of the volume of the steel fiber unsaturated polyester polymer concrete mixture.

[0027] Specifically, in this embodiment, the basic physical properties of the unsaturated polyester resin are: density: 1.05-1.10 g / cm 3 , viscosity is 400-600MPa.s, acidity is 18-24mgKOH / g, and solid content is 63-69%.

[0028] Specifically, in the present embodiment, the steel fiber is an end hook type steel fiber; the diameter of the end hook type steel fiber is 0.75-0.85 mm, the length is 30-35 mm, the density is 7.85 g / cm3, the elastic modulus is 210 GPa, and the tensile strength is 400 MPa.

[0029] Specifically, in this embodiment, the particle size of the natural crushed stone is 5 mm to 19 mm, and the particle size of the natural river sand is less than 4.75 mm.

[0030] Specifically, in this embodiment, a method for preparing steel fiber unsaturated polyester polymer concrete for emergency road repair comprises the following steps:

[0031] Step S1. Mix all solid materials, including cement, natural river sand, natural crushed stone and steel fiber, in a concrete mixer for 60 seconds to obtain dry concrete;

[0032] Step S2. adding a curing agent to the unsaturated polyester resin, stirring for 30 seconds to obtain a mixture, and then adding an accelerator to the mixture and mixing for another 30 seconds to obtain a resin mixture;

[0033] Step S3. Add the resin mixture obtained in step S2 into the concrete mixer and mix it with the dry concrete for 120 seconds;

[0034] Step S4. Pour the mixture into a designed steel mold, compact it by tamping without vibration, and demould it after curing at room temperature for 3 hours. Then, cure the specimen under natural conditions indoors until it reaches the corresponding age for experiment.

[0035] Examples 1-4

[0036] The steel fiber dosage in Examples 1-4 of the present application is the external admixture volume percentage dosage, specifically according to the configuration of the steel fiber unsaturated polyester polymer concrete in the following table, the steel fiber is added by volume, and the dosage is 0.5%, 1.0%, and 1.5% respectively, and the mixing ratio is shown in the table:

[0037] Table 1 Mixing ratio

[0038]

[0039] Note: The above materials are in volume percentage for steel fiber and in mass percentage for other ingredients.

[0040] The configuration of SF-UPPC is mixed in a specific order as described below. First, all the solid materials, including cement, dry sand, dry crushed stone and steel fiber, are mixed in a concrete mixer for 60 seconds. Then, the curing agent is added to the resin and mixed for 30 seconds, and then the accelerator is added to the mixture and mixed for another 30 seconds. Finally, the resin mixture is added to the concrete mixer and mixed with the solid materials for 120 seconds. The mixture is poured into the designed steel mold, compacted by tamping without vibration, and demoulded after curing at room temperature for 3 hours. The specimens are then cured under natural conditions indoors until they reach the corresponding age for experiment.

[0041] Test results

[0042] A total of 63 specimens were prepared in this study, of which 42 cubic specimens with a side length of 100 mm and 21 cylindrical specimens with a diameter of 150 mm and a height of 300 mm were used for quasi-static tests. According to the existing laboratory equipment, a MATEST material compression testing machine with a load limit of 4000 kN was used to carry out axial compression tests on the cylinders (e.g. Figure 1 In order to clearly observe the entire failure process of the specimen and accurately record the stress-strain curve, this test refers to the recommendations in the US specification (ASTM Designation: C 39-96), using equal displacement loading control and a loading rate of 0.18 mm / min. The test device used is as follows: Figure 2 The test results are shown in Table 1. The load, compression displacement and strain of the specimen were measured by a JM3813 multifunctional static strain tester ( Figure 2As shown in the figure, the data is collected synchronously and the collection frequency is once per second. In order to avoid stress concentration caused by the discreteness of the internal structure of the specimen and the unevenness of the pressure-bearing surface, the specimen is preloaded according to the elastic modulus test step 8.0.4 in GB50081-2002. Each specimen is preloaded three times, and the vertical compression displacement and longitudinal hoop strain values ​​in the collector are observed. When the change value between each pair of data does not exceed 10%, the formal loading test can be started. Before loading, the shutdown load is set to 20% of the peak load. Figure 3 As shown in the figure, since it is vibration-free concrete, with the increase of steel fiber content, the pores in the concrete become more and more numerous and larger. When the steel fiber volume content reaches 1.5%, the concrete has already appeared honeycombed surface. Therefore, SF1.5-UPPC with a content of 1.5% is not studied in this study.

[0043] The static compression test results are shown in Table 2 and Figure 4 As shown in Table 3, with the increase of curing age, the compressive strength and splitting strength of SF-UPPC increase, and the growth is fastest in the initial 6 hours; the compressive strength and splitting tensile strength of the sample cured for 6 hours reach 50-60% of the 28-day strength, the compressive strength of the sample cured for 7 days reaches 81% of the 28-day strength, and the splitting tensile strength of the sample cured for 7 days reaches 91% of the 28-day strength. It can be seen from Table 3 that with the increase of steel fiber content, the compressive strength increases, and the increase can reach 60%.

[0044] Table 2 Compressive strength (MPa)

[0045]

[0046] Static compression tests were carried out on cylindrical specimens at different curing ages. The results are shown in Table 3 and Figure 5 As shown. Figure 5 In the equation, positive strain refers to the compressive strain measured along the longitudinal direction of the cylindrical specimen, while negative strain refers to the circumferential expansion strain measured in the transverse direction of the same specimen. Figure 5 It can be seen from the static stress-strain curve in (a) that the static stress-strain curves of UPPC at different curing ages have similar trends and can be mainly divided into three parts: the initial approximate linear elastic stage, followed by the nonlinear increase in stress, and finally the softening stage leading to complete destruction. The nonlinear increase stage of stress mainly includes the compression and compaction of internal tiny pores and concrete cracks. When the concrete reaches the densest state, the stress reaches the maximum value, and then the tiny pores begin to collapse and the cracks begin to expand, thus forming a crack, leading to the destruction of the concrete. This stage lasts the longest during the test. The compressive strength, elastic modulus, Poisson's ratio, and circumferential peak strain increase significantly with the increase in curing age, but the elastic deformation capacity and the strain corresponding to the peak stress decrease. Figure 5 As shown in (d), there is a linear growth relationship between the elastic modulus and the compressive strength.

[0047] Table 3 Test results

[0048]

[0049] The above results show that: with the increase of curing age, the compressive strength of UPPC increases, and the growth is fastest within the initial 6 hours, with high early strength; the compressive strength of the sample cured for 6 hours under natural conditions reaches 50-60% of that of 28 days, and the compressive strength of the sample cured for 7 days reaches 81% of that of 28 days, with super early strength characteristics. At the same time, with the increase of steel fiber content, the compressive strength of concrete increases, but the elastic modulus does not change much; with the increase of steel fiber content, the working performance of concrete deteriorates, so the most suitable volume content of steel fiber is 1.5%.

[0050] The technical solutions provided by the embodiments of the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the embodiments of the present invention. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. At the same time, for those skilled in the art, according to the embodiments of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A steel fiber unsaturated polyester polymer concrete used for emergency road repair, characterized in that: The steel fiber unsaturated polyester polymer concrete is composed of the following components in a mass ratio: unsaturated polyester resin: curing agent: accelerator: cement: natural river sand: natural crushed stone = 6.8:1:0.5:7.6:34:41.6, wherein the amount of steel fiber accounts for 0-1.5% of the volume of the steel fiber unsaturated polyester polymer concrete mixture.

2. The steel fiber unsaturated polyester polymer concrete used for road emergency repair according to claim 1, characterized in that: The basic physical properties of the unsaturated polyester resin are: density: 1.05-1.10 g / cm 3 , viscosity is 400-600MPa.s, acidity is 18-24mgKOH / g, and solid content is 63-69%.

3. The steel fiber unsaturated polyester polymer concrete used for road emergency repair according to claim 1, characterized in that: The steel fiber is an end hook type steel fiber; the diameter of the end hook type steel fiber is 0.75-0.85 mm, the length is 30-35 mm, the density is 7.85 g / cm3, the elastic modulus is 210 GPa, and the tensile strength is 400 MPa.

4. The steel fiber unsaturated polyester polymer concrete used for emergency road repair according to claim 1, characterized in that: The particle size of the natural crushed stone is 5 mm to 19 mm, and the particle size of the natural river sand is less than 4.75 mm.

5. A method for preparing steel fiber unsaturated polyester polymer concrete for road emergency repair, characterized in that: The following steps are involved: Step S1. Mix all solid materials, including cement, natural river sand, natural crushed stone and steel fiber, in a concrete mixer for 60 seconds to obtain dry concrete; Step S2. adding a curing agent to the unsaturated polyester resin, stirring for 30 seconds to obtain a mixture, and then adding an accelerator to the mixture and mixing for another 30 seconds to obtain a resin mixture; Step S3. Add the resin mixture obtained in step S2 into the concrete mixer and mix it with the dry concrete for 120 seconds; Step S4. Pour the mixture into a designed steel mold, compact it by tamping without vibration, and demould it after curing at room temperature for 3 hours. Then, cure the specimen under natural conditions indoors until it reaches the corresponding age for experiment.